Linking litter decomposition to soil physicochemical properties, gas transport, and land use. Issue 1 (27th December 2021) - Fu, Yuting; de Jonge, Lis W.; Greve, Mogens H.; Arthur, Emmanuel; Moldrup, Per; Norgaard, Trine; Paradelo, Marcos
Abstract: Litter decomposition is a critical process in carbon cycling, which can be affected by land use. The relationship between litter decomposition and soil properties under different land uses remains unclear. Litter decomposition can be quantified by the Tea Bag Index (TBI), which includes a decomposition rate k and a stabilization factor S . Our objective was to investigate linkages between TBI and soil physicochemical and gas transport properties and land use. We buried three pairs of tea bags in 20 sites (covering cropland, grassland, heathland, and forest land uses) in a transect from the western to the eastern coast of the Jutland peninsula, Denmark. The tea bags were retrieved after 90 d and TBI was determined. Disturbed and undisturbed (100 cm 3 soil cores) samples were collected from each site. Thereafter, clay content, organic carbon (OC), bulk density (ρb ), pH, electrical conductivity (EC), oxalate‐extractable phosphorus (Pox ), aluminum (Alox ), and iron (Feox ) content, soil water content, gas diffusivity ( D p / D 0 ), and air permeability ( k a ) at −10 kPa were measured. Results showed that grasslands had the highest k and S among four land uses, and agricultural soils (croplands and grasslands) exhibited higher TBI values than seminatural soils (forest and heathland). The prediction of S was better than that of k based on multiple linear regression analysis involving soil physicochemical properties. Clay content and OC were not strong predictors. Including D p / D 0 and k a improved the prediction of S, and finally, the inclusion of land use enhanced the prediction of both k and S . The different trends between two distinct land‐use groups can be attributed to pH, Pox, and ρb . Core Ideas: Litter decomposition, quantified by the Tea Bag Index (TBI), was determined across land uses. Grasslands had the highest decomposition rate and stabilization factor of plant litter. Soil gas transport was more important to stabilization factor not decomposition rate. Variability in the TBI parameters was affected by soil pH, Pox, and ρb . The inclusion of land use improved the predictions of both TBI parameters.